Abdominal aortic aneurysm infected by Yersinia enterocolitica (Actualizaciones en Sida e Infectología, 2023)
Main clinical manifestations of Yersinia enterocolitica infections are acute gastroenteritis and pseudoappendicitis. Although extra intestinal complications have been documented, vascular infections are very rare. We report a case of Yersinia enterocolitica infection of an aortoabdominal aneurysm in a 78-year-old male patient with previous history of aneurysm. The patient was admitted to the Emergency Department with a condition of acute abdomen; after performing an angiotomography, he underwent aortic vascular replacement with homograft because of suspicion of rupture. He evolved with shock, multiple organ system failure and died shortly after surgery. Y. enterocolitica was recovered from cultures of aorta and thrombus. Pathogenesis of this infection may be related to release of septic emboli arising from endocarditis or bacteremia, or by contiguous foci of infection. Suspected diagnosis was infection of the aortic aneurysm by an adjacent intestinal infection though no previous symptoms, such as diarrhea, were documented. Cardiac echodoppler showed no evidence of bacterial endocarditis.
Keywords: Mycotic aneurysm, Yersinia enterocolitica infection, aortic aneurysm